Targeting Phospholipid Metabolism in Cancer - Cheng, Menglin; Bhujwalla, Zaver M.; Glunde, Kristine (Frontiers in Oncology, 2016)
All cancers tested so far display abnormal choline and ethanolamine phospholipid metabolism, which has been detected with numerous magnetic resonance spectroscopy (MRS) approaches in cells, animal models of cancer, as well as the tumors of cancer patients. Since the discovery of this metabolic hallmark of cancer, many studies have been performed to elucidate the molecular origins of deregulated choline metabolism, to identify targets for cancer treatment, and to develop MRS approaches that detect choline and ethanolamine compounds for clinical use in diagnosis and treatment monitoring. Several enzymes in choline, and recently also ethanolamine, phospholipid metabolism have been identified, and their evaluation has shown that they are involved in carcinogenesis and tumor progression. Several already established enzymes as well as a number of emerging enzymes in phospholipid metabolism can be used as treatment targets for anticancer therapy, either alone or in combination with other chemotherapeutic approaches. This review summarizes the current knowledge of established and relatively novel targets in phospholipid metabolism of cancer, covering choline kinase α (ChKα), phosphatidylcholine-specific phospholipase D1 (PLD1), phosphatidylcholine-specific phospholipase C (PtdCho-PLC), sphingomyelinases (SMAs), choline transporters, glycerophosphodiesterases, phosphatidylethanolamine N-methyltransferase (PEMT), and ethanolamine kinase (ETKN). These enzymes are discussed in terms of their roles in oncogenic transformation, tumor progression, and crucial cancer cell properties such as fast proliferation, migration, and invasion. Their potential as treatment targets are evaluated based on the current literature.